If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 + -2x = 8 Reorder the terms: 2 + 5x + -2x = 8 Combine like terms: 5x + -2x = 3x 2 + 3x = 8 Solving 2 + 3x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = 8 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = 8 + -2 3x = 8 + -2 Combine like terms: 8 + -2 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 9n^2+16=-24n | | 5+5x=-50 | | 5x+-2-2x=8 | | 6(2x-1)-12=7+12(x+1) | | -0.875-(-n)=-0.583 | | m+6m+5m+8= | | 9=-5p+5+6p | | 4(2x+5)-18=36 | | -3=9p-9-8p | | (8)(16)=(6)(2x+6) | | 4=3p+6-2p | | -9x=-10x | | -3=-5p+9+6p | | 1-0.7k=1 | | -9=7p-15-6p | | 12xy^2+1=0 | | 24=5X-7 | | 3=3p-4-2p | | 17+9s=2(8s-3) | | 30-5(p-10)=11 | | 16x^2+3=-16x | | -14=4p+7-3p | | 6x+10=2y+10 | | -14=-8p+5+9p | | (x+1)/(2-x)*(2-x)^2/(x-2)*2/x+1 | | -11w+6=-38 | | .24.14= | | 10=-2p-2+3p | | -4=-4p-11+5p | | M/-16=-9 | | y-9=15(x-5) | | 13=3p-15-2p |